ANALISIS PENGARUH PENDIDIKAN, UPAH MINIMUM PROVINSI DAN BELANJA MODAL TERHADAP KETIMPANGAN PENDAPATAN DI SELURUH PROVINSI DI INDONESIA - Muhammad Anshari; Zul Azhar; Ariusni Ariusni (Jurnal Ecogen, 2018)
This study aims to determine and analyze the influence of education, provincial minimum wages and capital expenditure on income inequality in Indonesia. This type of research is associative descriptive research, where the data used is secondary data from 2012 to 2017 obtained from related institutions and institutions, which were analyzed using panel regression method. The findings of this study indicate that education has a negative and insignificant effect on income inequality in provinces in Indonesia, provincial minimum wages have a negative and significant effect on income inequality in provinces in Indonesia, capital expenditure has a positive and significant effect on income inequality in provinces in Indonesia. Taken together education, provincial minimum wages, capital expenditure has a significant effect on income inequality in provinces in Indonesia. Keywords: income inequality, education, minimum wage, capital expenditure